The Potential of Exosomal RNAs in Atherosclerosis Diagnosis and Therapy - Yang, Wenzhi; Pan, Xudong; Ma, Aijun (Frontiers in Neurology, 2021)
Atherosclerosis is an inflammatory disease that can lead to cardiovascular disorders and stroke. In the atherosclerosis microenvironment, exosomes secreted from various cells, especially macrophage-derived exosomes, play an important role in cell–cell communication and cellular biological functions. In this article, we review previous studies on exosomal RNAs and discuss their potential value in atherosclerosis diagnosis and therapy. Based on our research, we concluded that macrophage exosomes have potential value in atherosclerosis diagnosis and therapy. However, there is a need for future studies to further investigate methods of exosome isolation and targeting.